Reflections on the nature of rapport within suspect interviews. Issue 2 (3rd April 2022) - Crough, Quintan; Dion Larivière, Cassandre; Snow, Mark D.; Eastwood, Joseph
ABSTRACT : Rapport building has been highlighted as an effective and ethical means of eliciting information from suspects within criminal investigations. The purpose of this contemporary comment is to distinguish between what we have termed 'interrogative rapport' from rapport-building practices that occur in other professional contexts. To support this distinction, we advance the following arguments: (1) interrogative rapport is actively and intentionally created by the interviewer; (2) the goal of actively building rapport is to persuade the suspect to comply with requests for information; (3) interrogative rapport is inherently deceptive; and (4) the interviewer's goal of rapport building—the elicitation of information from the suspect—is independent of, and often in opposition to, the suspect's best interests. We believe that by acknowledging the outlined elements of interrogative rapport, more nuanced discussions concerning both rapport and persuasion within suspect interviews will result.